Analisis Strategi Peningkatan Kinerja dengan Servant Leadership, Organisasi Pembelajar dan Kompetensi Sebagai Variabel Intervening - Chesar Rahmadi (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2020)
This study analyses the influence of strategy servant leadership, competencies, and learning organisation on official performance, the influence of strategy servant leadership with competencies intervening variables on official performance, and the influence of learning organisations with competencies as variables intervening on official performance. There are 127 respondents in the Regional Office of Manpower and Transmigration Department DKI Jakarta. The analysis data technique in this research uses Structural Equation Modelling (SEM) analysis operated by the Analysis of Moment Structure (AMOS) 22 program. This study shows that strategy servant leadership, learning organisations, and competencies are significant positive effect (5,163); on official performance Regional Office of Manpower and Transmigration Department DKI Jakarta. All variables influence official performance.